Early Detection And Management Of Pneumonia After Measles Infection (Open Herald: Periodical of Methodical Research, 2025)
Measles remains a significant global health concern, particularly in regions with low vaccination coverage. One of the most severe complications of measles is pneumonia, a leading cause of measles-associated mortality. This article explores the importance of early detection and effective management of pneumonia following measles infection. Through a review of current literature and clinical guidelines, we highlight the clinical presentation, diagnostic methods, and treatment strategies for post-measles pneumonia. Emphasis is placed on the role of vaccination, early antibiotic intervention, and supportive care in reducing morbidity and mortality. The findings underscore the need for heightened clinical awareness and integrated healthcare approaches to improve outcomes in affected populations